OVARIAN CANCER: MOST FREQUENTLY SEEN GYNAECOLOGICAL MALIGNANCY IN ZIAUDDIN HOSPITAL, NORTH NAZIMABAD - Shama Chaudhry; Hina Rajani; Rubina Hussain; Azlaan Naqvi (ziauddin University, 2024)
Background: The prevalence of genital tract malignancies is rising worldwide making it one of the most common malignancies in females after breast cancer. Despite cervical cancer being the most commonly occurring cancer globally, a multitude of studies in Pakistan have identified ovarian cancer as the most commonly occurring malignant tumor. The morbidity and mortality rates from genital tract tumors are considerably higher in developing countries. In developed countries, screening tests for early diagnosis of a malignancy followed by effective treatment are readily available. The objective of this study is to study the pattern and relative frequency of the malignancies involving the genital tract among women admitted to Ziauddin Hospital in 2015. Methods: The study is a retrospective, observational analysis of the case files of female patients admitted into Ziauddin University Hospital, North Nazimabad. The patients coming to the OPD have been followed for the last 3 years to check for the suspected presence of a genital tract malignancy. Results: A total of 55 patients over the last three years were confirmed to have some form of genital tract malignancy. Ovarian cancer accounted for 49% of the outcome, with around 23.6% of the cases diagnosed at stages 3 and 4. Endometrial cancer was the second most common cancer, with 27.2% being diagnosed at stage 1. Cancers of the cervix and vulva accounted for 3.6% and 1.8% respectively. No cancer of the vagina was documented. Conclusion: The most common genital tract malignancy in female patients at Ziauddin University Hospital is ovarian cancer, in contrast to the vast majority of developing countries where cervical cancer is the leading cause of genitourinary malignancies.